Antifungal Activity of Rhamnolipid Biosurfactant Produced by Pseudomonas aeruginosa A4 against Plant Pathogenic Fungi - Onlamool, Theerawat; Saimmai, Atipan; Maneerat, Suppasil (Trends in Sciences, 2022)
Biosurfactants have been shown to have a variety of other agricultural applications. Antimicrobial activity is a desirable property in a variety of biosurfactants. Several biosurfactants produced from bacteria have antibacterial activity against plant diseases, making them a promising biocontrol molecule for ensuring agricultural sustainability in the long run. The purpose of this research was to characterize biosurfactant produced at different carbon source by biosurfactant-producing bacterial strains isolated from contaminated soapstock sediment, as well as its antifungal properties. Biosurfactant-producing bacteria were isolated from soapstock-contaminated soil which bacteria were selected by using drop collapse and oil displacement tests. Twelve isolates reduced surface tension of culture broth from 50 to 31 - 43 mN/m. According to 16S rRNA sequence analysis, these isolates belong to 8 different genera (Acinetobacter, Citrobacter, Enterobacter, Klebsiella, Pantoea, Pseudomonas, Stenotrophomonas and Xanthomonas). The supernatant of Pseudomonas aeruginosa A4 grown in MSM supplemented with soapstock was the most effective biosurfactant against Aspergillus flavus F2, Aspergillus niger F14, Cunninghamella bertholletiae F1 and Rhizopus oryzae F5, inhibiting mycelium growth by 54, 61 59 and 50 %, respectively. The extract substance inhibited spore germination against A. flavus F2 and R. oryzae F5 with a minimum inhibitory concentration of 2.75 mg/mL. TLC, FT-IR, ESI-MS and GC-MS analysis demonstrated that the mono-rhamnolipids and di-rhamnolipids had the same 3-hydroxy fatty acid composition of C8, C10 and C12. Overall, the biosurfactant-producing strains identified in this investigation show promise for future development and application in cost-effective industrial-scale biotechnological processes. HIGHLIGHTS Biosurfactant producing bacteria were isolated from soapstock contaminated soil The supernatant of Pseudomonas aeruginosa A4 grown in MSM supplemented with soapstock was the most effective biosurfactant against plant pathogenic fungi Biosurfactant from Pseudomonas aeruginosa A4 was identified as rhamnolipid comprising of both mono and di-rhamnolipid congeners GRAPHICAL ABSTRACT